The experimental and theoretical study on the influence of alkali metals on the electronic charge distribution in five-membered aromatic acids (2-thiophenecarboxylic, 2-furanecarboxylic and 2-pyrrolecarboxylic acids). (5th September 2015) - Świderski, G.; Kalinowska, M.; Wojtulewski, S.; Lewandowski, W.
Graphical abstract: The strength of the perturbation of the electronic charge distribution in the aromatic ring of salts of 5-membered heteroaromatic acids depended on the kind of alkali metal cations and changed along with the series of Li → Cs compounds. Alkali metal cations perturbed the structure of heterocyclic acids depending on the kind of heteroatom in the ring. Abstract: In the work the effect of alkali metal cations on the electronic system of heterocyclic five-membered heterocyclic acids that possess S, N and O atoms was studied (2-thiophenecarboxylic, 2-furanecarboxylic and 2-pyrrolecarboxylic acids). The experimental (IR, Raman, NMR) and theoretical (in B3LYP/6-311++G ∗∗ and MP2/6-311++G ∗∗ levels) methods were applied in this study. The studies showed that formation of alkali metal salts of the aromatic and heteroaromatic six-membered acids caused perturbation of the aromatic system of ligand. The strength of the perturbation of the electronic charge distribution in the aromatic ring and carboxylate anion of salts depended on the kind of alkali metal cations and changed along with the series of Li → Na → K → Rb → Cs compounds. Alkali metal cations perturbed the structure of heterocyclic acids depending on the kind of heteroatom in the ring. Ionic potential and ionization energy were the main parameters of metal cation which decided on the electronic charge distribution in salt molecules.